The association of IL-1β, IL-1α, IL-6, and E-selectin with the diastolic dysfunction in patients with type 2 diabetes mellitus and preserved ejection fraction - Marinković, Dejan M.; Dragović, Tamara; Djurić, Predrag; Rakočević, Jelena; Malović, Dragana; Kiković, Saša; Stanojević, Ivan; Dejanović, Bratislav; Ristić, Petar; Hajduković, Zoran (Vojnosanitetski pregled, 2025)
Background/Aim. The importance of chronic inflammation, endothelial dysfunction, certain cytokines, and selectins in the development of type 2 diabetes mellitus (T2DM) and cardiovascular diseases (CVDs) is increasingly evident and supported by evidence. However, the role of chronic inflammation in the development of diastolic dysfunction (DD) in the early stages of cardiomyopathy in T2DM patients is insufficiently studied. The aim of this study was to examine the possible association of interleukin (IL)-1β, IL-1α, IL-6, and E-selectin with DD in T2DM patients with still preserved ejection fraction (EF). Methods. The research included a total of 74 subjects divided into two groups: a group with proven T2DM, i.e., diabetes group (DG) (n = 45), and a healthy control group (HCG) (n = 29). Echocardiographic parameters of DD and serum levels of IL-1β, IL-1α, IL-6 and E-selectin were compared between the two groups, and the correlation of echocardiographic parameters of DD and serum biomarkers was examined in both groups. Results. Subjects with T2DM had significantly different values of DD parameters compared to HCG but also higher values of IL-6 (19 pg/mL vs. 12 pg/mL, p = 0.002), E-selectin (2,036 pg/mL vs. 1,522 pg/mL, p
Keywords: biomarkers; cardiomyopathies; cardiovascular diseases; cytokines; diabetes mellitus, type 2; echocardiography; heart failure